Analysis of microbiological and chemical risks in fresh and smoked fishes sold in Togo - Bouka, Ekpetsi Chantal; Lawson-Evi, Povi; Idoh, Kokou; Paka, Essodolom; Eklu-Gadegbeku, Kwashie (International journal of Rural Development, Environment and Health Research, 2021)
The diseases due to fish contamination are an important public health concern worldwide particularly histamine ﬁsh poisoning. Histamine is produced during bacterial decarboxylation of the histidine present in fish muscles. The aim of this study is to analyze microbiological and chemical factors of degradation of fresh fish at Lomé fishery port and assess histamine content in smoked fish sold in local market. The method of European Regulation has been used to determine Total volatile base nitrogen (TVBN) and the content of histamine was performed by Agilent 1290 Infinity II HPLC. The standard NF V08-051: 1999 was used for the count of microbial colonies expressed in colony forming units (CFU/ml). The results show that 100% of fresh fishes were highly contaminated by total aerobic flora (225 0000 CFU/g), Thermotolerant coliforms (88750 CFU/g) and E. coli (103 920 CFU/g). The content of Total volatile base nitrogen (TVBN) of anchovies and sardinella was ranged from 23.34 ± 0.23 to 103.14 ± 0.27 mg/100g. Smoked fishes from three markets have shown higher histamine mean levels varying from 295.06 to 746.54 mg/kg. These results show that Togolese are exposed to high concentrations of histamine when consuming smoked fish. Determination of histamine is very important due to its toxicity for humans and as an indicator of the freshness of fish and fish products.